PROSES GANTI RUGI LAHAN BENDUNGAN TEMEF KABUPATEN TIMOR TENGAH SELATAN DITINJAU DARI UNDANG-UNDANG NOMOR 2 TAHUN 2012 TENTANG PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM - Manafe, Andry Samuel; Jacob, Yossie M Y; Dinata, Husni Kusuma (Petitum Law Journal, 2025)
The practice of land acquisition for the public interest, especially the construction of the Temef Dam, has caused problems between the government and the community, especially in terms of land acquisition. Starting from compensation for the land that has been acquired and the time of land acquisition or relocation of the community. The implementation of land acquisition for public interest often experiences obstacles and challenges. The application of a fair compensation mechanism in the construction of Temef Dam in South Central Timor Regency is important considering the potential for conflict that can arise between the landowner community and the government. These conflicts can arise due to various factors, such as disagreements over compensation values, late payments, or lack of information provided to the community. Therefore, the principles stated in Law Number 2 of 2012 concerning Land Acquisition for Development in the Public Interest, such as transparency, justice, and consensus, must be implemented properly so that the land acquisition process can take place peacefully and meet the interests of all parties. These inhibiting factors illustrate some of the fundamental challenges that often arise in land acquisition projects, especially in the context of the Temef Dam construction. The discrepancy in compensation values ​​is one of the biggest factors that triggers community objections. Local communities often feel that the compensation offered does not reflect the market value or potential economic benefits of their land, especially for land used for agriculture or other productive economic activities.